May We Continue Informing or May We Assume the Change? - María Orfa Rojas; Ruth Garzón; Lilia del Riesgo (Revista Ciencias de la Salud, 2006)
Traditional educative systems, had convertstudents in passive recipient, who are keepingRecibido: Marzo 3 de 2006.Aceptado: Abril 17 de 2006.* Ph.D, Profesora titular.** Ph.D, Profesora principal.+ M.D., MSc, Profesora principal, Unidad de Bioquímica,Instituto de Ciencias Básicas, Facultad de Medicina,Colegio Mayor Universidad del Rosario.Autor correspondiente: María Orfa Rojas, Unidad deBioquímica, Facultad de Medicina de la Universidaddel Rosario, mariaorfarojas@yahoo.comArtículo de reflexióninformation without any possibility to processand apply it for the solution of daily problems.General discussion between educative researchers,had been establish the necessity to changethe educative strategies that have been supportingthose situations, looking for an integraleducation of the individual in terms of the capacityto argue, to create, to innovate, to developby him self with independence.Governments, institutions and the politicsrequirements, that handle the globalization andthe human development based in the knowledgeeconomy, demand changes in the pedagogicalsystem strategies in spite of the barriers fromthe traditional educative system. Responding tothese necessity, the Biochemistry Departmentbelong to the Basic Sciences Institute from theMedicine Faculty in the University of Rosario,is applying a different pedagogical strategy.